Fruit growth in three ecotypes of dry-season Spondias purpurea L. - Alia Tejacal, Irán; Cancino-Labra, Samuel; López-Martínez, Víctor; Juárez-López, Porfirio (Acta Universitaria, 2023)
Mexican plum is a tropical fruit widely consumed fresh. Although it has a high diversity, there is not enough research on fruit growth kinetics. The objective of this work was to determine a series of physical, chemical, and physiological changes during fruit growth. Trees of three ecotypes were evaluated, from fruit set to physiological maturity. Results revealed a rapid increase of fruit respiration in the three fruit ecotypes between the day 30 and 60 of the fruit growth, although respiration decreased afterwards; likewise, a similar behavior was observed with the titratable acidity. Flavor index was higher in Amarilla (12.2) than in Morada and Roja. Thus, fruit growth in these ecotypes of Mexican plum appeared to be double sigmoidal with 90 days of duration, where the titratable acidity, flavor index, polar diameter, luminosity, and chromaticity help to differentiate among them.